Examining marriage and family therapists in non-traditional areas of application: an ecological systems theory of creativity approach - DuPree, William Jared (Kansas State University, 2007)
Marriage and family therapists (MFTs) over the past twenty years have increased their visibility by using their clinical skills and a systemic framework in other areas outside of therapy (i.e., business, school, medicine). Many of these individuals have pioneered roads of systems theory application through a creative process. Traditional creativity research has focused mainly on individual factors. However, Csikszentmihalyi’s theories of flow and creativity have offered important insight on the systemic nature of the creative process. Recently, research regarding intrinsic motivation and group creativity has provided more insight on how Csikszentmihalyi’s theory could be further developed. Furthermore, applying an ecological systems theory framework to his current model provides additional levels of influence to be examined in regards to maximizing creative potential in individuals and groups. Using deductive and inductive methodologies, an ecological systems theory of creativity is presented providing a framework for studying how MFTs that have successfully entered into non-traditional realms of systemic application go through the creative process of entering into their endeavors. Interviews with successful MFTs applying skills in non-traditional areas of applications were conducted using a modified phenomenological approach. Creative processes were outlined based on themes and patterns that emerged during the analysis. Implications of these findings are made regarding how to improve creativity in MFTs at the individual, academic, and professional field levels. In addition, implications are made regarding how to improve student recruitment and maximize potential in MFT trainees. Finally, implications regarding the maximization of productivity in university settings and applying systemic creativity to business, school, government, and education settings are presented.
Keywords: Creativity; Family therapy; Flow; Systems theory; Standpoint theory; Maximizing productivity; Education, Higher (0745); Education, Social Sciences (0534); Psychology, Social (0451)